The stereoselective birch reduction of pyrroles - Donohoe, T; Guyo, P; Helliwell, M (1999)
The Birch reduction has been applied to electron-deficient pyrroles substituted with a chiral auxiliary at the C-2 position. Using either 8- phenylmenthol or trans-2-(α-cumyl)cyclohexanol (TCC) as auxiliaries, high levels of stereoselectivity were obtained. Moreover, the auxiliary could be removed using a high-yielding three-step sequence to furnish substituted dehydroproline derivatives with high enantiomeric purity. By choosing either (-)-8-phenylmenthol or (+)-TCC as an auxiliary either enantiomer of the dehydroproline product could be obtained.